P-018 Effect of pitavastatin on preventing ischaemic complications with carotid artery stenting: a multicentre prospective study. (14th July 2013) - Takayama, K; Myouchin, K; Ikeda, N; Sakamoto, M; Nakagawa, I; Wada, T; Masuo, O; Nakahara, I; Tanemura, H; Toma, N; Maeda, M; Suzuki, H; et al.
Abstract : Background: Carotid artery stenting (CAS) is becoming an alternative to carotid endarterectomy (CEA). However, periprocedural ischaemic stroke is one problem associated with CAS. Statin therapy can reportedly reduce periprocedural complication rates in coronary intervention. This study was designed to assess whether preoperative statin therapy reduces the risk of periprocedural ischaemic complications with CAS. Material and Methods: In this prospective study at 11 centres, patients with carotid stenosis (symptomatic ≥50%, asymptomatic ≥80%) and at high risk of requiring CEA, but without previous statin treatment were divided into two groups by low-density lipoprotein cholesterol level (LDL-C). With LDL-C≥120 mg/dl, the previous stain (PS) group received pitavastatin at 4 mg/day for 4 weeks. With LDL-C <120 mg/dl, the non-PS group received no statin therapy for 4 weeks. After 4 weeks, both groups underwent CAS. Frequencies of new ipsilateral ischaemic lesions on diffusion-weighted imaging (DWI) within 72 h after CAS and major adverse events (MAEs) (defined as transient ischaemic attack, stroke, myocardial infarction or death) within 30 days were assessed. Results: Among the 80 patients enrolled, 61 patients (PS group, n=31; non-PS group, n=30) fulfilled the inclusion criteria. New ipsilateral ischaemic lesions were identified in 8 of 31 patients (25.8%) in the PS group and 16 of 30 patients (55.3%) in the non-PS group (P=0.027). MAE occurred in 0 patients in the PS group and in 3 of 30 patients (10.0%) in the non-PS group (P=0.07). Conclusion: Pretreatment with pitavastatin significantly reduced the frequency of periprocedural ischaemic complications associated with CAS. Disclosures: K. Takayama: None. K. Myouchin: None. N. Ikeda: None. M. Sakamoto: None. I. Nakagawa: None. T. Wada: None. O. Masuo: None. I. Nakahara: None. H. Tanemura: None. N. Toma: None. M. Maeda: None. H. Suzuki: None. W. Taki: None.